Wind Tunnel Experiment Of Aeroelastic Flutter - Mah, Chuen Tak (Universiti Sains Malaysia, 2018)
In this work, flutter behaviour of NACA 6409 is investigated using wind tunnel. The plunging and pitching oscillation of the wing is being observed to determine the dynamic instability point. The elastic axis will be manipulated in the experiment where the position of the elastic axis was varied at 25% 50% and 75% of the wing chord to determine the critical flutter speed. The effects on flutter speed at different elastic axis was discussed and analysed to explain the phenomenon. The method of designing and fabrication of the wing model and rig was presented step by step in the thesis. In the experiment the results show that the flutter speed for the elastic axis at 25% of the wing chord is the highest which is 17.84 m/s and follow by the elastic axis at 50% of the wing chord with the flutter speed of 16.36 m/s and lastly is the elastic axis at 75% of the wing chord with the flutter speed of 13.34 m/s. The causes affecting the flutter speed is also discussed. Then flutter suppression experiment was conducted. Active control method using aileron was employed in this research to evaluate the possibility in suppressing flutter oscillation. Autopilot system was installed on the rig of the experiment. The autopilot consisted of a gyro sensor in which it detects the pitching motion of the wing. The idea of the suppression method is to use the autopilot system to detect the pitching motion, and generate signal to be sent to the servo for controlling the motion. The signal is the response that is generated by the PID controller system in the autopilot. The flutter suppression experiment was carried out at the flutter speed of the elastic axis at 50% of the wing chord. The results showed that flutter was suppressed by the autopilot system.